Estudio de factibilidad para la implementación de un edificio parqueadero, cantón Quevedo, año 2014. - Silva Varela, Blanca Angélica (2015)
The urban transport system in the city of Quevedo, consists of a network of vehicles of heavy and light transport, sorting each of them affects the daily activities of the city causing problems in traffic flow is traditional parking on the streets, which prevents use those spaces to maintain better traffic flow, inadequate form of parking on the streets cause congestion bringing the lack of access to motor vehicles. Parking affect people, trade, taxi, Among others. In Ecuador there is a very large fleet it is growing especially in the city of Quevedo, given that local parking not meet the needs in an appropriate way, the idea of building parking lot for the city. The aim of the research is to analyze the feasibility of building a parking building in the city of Quevedo that allows organizing and optimizing space for parking and thus contributing to the planning of the city. In the first part of a market study was conducted seeking to identify unmet demand on the implementation of a parking building in the city of Quevedo, which would lead to meet the urgent needs of the citizens to have a parking and to help improve the existing traffic congestion.